„Je est un autre“ - Alfred Prédhumeau (Recherches Germaniques)
France and the French play an important role in Döblin’s biography, as his adoption of French nationality shows. This contribution, which is based on a few works from the exile period, will show how the author’s relationship to French alterity is reflected in his literary production. Our reading will focus on the relevant passages from the Babylonische Wandrung, the Schicksalsreise and November 1918. Compared to the earlier texts published between 1917 and 1921, we can see that Döblin slowly underwent a significant paradigm shift: his changed French view on Germany is characterized by feelings of alterity; he himself had become an Other.